Fast Corner Detection in Augmented Reality Learning Management of the Corpse - Syaripudin, Undang; Ramdania, Diena Rauda; Widiawaty, Wine; Zulfikar, Wildan Budiawan; Maylawati, Dian Sa'adillah (Informatica, 2021)
50 out of 170 senior high school students do not understand the material of the corpse management practicum. This study aims to make it easier for students to understand better and remember caring for corpses in the classroom. A learning application for managing bodies made using Augmented Reality (AR) technology. The algorithm used is FAST Corner Detection. This algorithm's sequence is: resizing the image, changing the image to grayscale, smoothing the gray color (histogram), and determining the threshold as a determining point for the point marker. This application contains material on the procedures for bathing, bathing, praying, and burying the body. The FAST Corner Detection algorithm's performance takes 0.41 seconds to detect an object and can be done at a distance of 1 meter. The application also meets 82.8% of the user side's usability level, which indicates that this application is beneficial for learning. Interface testing gets a final score of 90.7%. This result suggests that the application is in outstanding criteria.